Two-Year Toxicity and Efficacy of Carbon Ion Radiotherapy in the Treatment of Localized Prostate Cancer: A Single-Centered Study - Li, Ping; Hong, Zhengshan; Li, Yongqiang; Fu, Shen; Zhang, Qing (Frontiers in Oncology, 2022)
Background: The purpose of this study was to retrospectively analyze the safety and feasibility of spot scanning carbon ion radiotherapy (CIRT) for patients with localized prostate cancer. Methods: 118 localized prostate cancer patients treated with spot scanning CIRT at Shanghai Proton and Heavy Ion Center (SPHIC) were enrolled in this study. The dose was gradually increased from RBE-weighted dose (DRBE) = 59.2Gy to 65.6Gy in 16 fractions. The primary endpoint was the acute and late toxicities. Secondary endpoints were biochemical relapse free survival (bRFS), distant metastasis free survival (DMFS), prostate cancer-specific survival (PCSS), and overall survival (OS). Results: The median follow-up time was 30.2 months (4.8-62.7 months). Acute grade 1 and 2 genitourinary (GU) toxicities were 15.3% and 18.6%, while acute grade 1 and 2 gastrointestinal (GI) toxicities were 2.5% and 0%, respectively. Late grade 1 and 2 GU toxicities were 4.2% and 1.7%, respectively. No late GI toxicity were observed. There were no cases of severe acute or late toxicity (≥grade 3). The significant association was not found between the factors and the acute GU toxicities except for clinical target volume (CTV) (p=0.031) on multivariate analysis. The 2-year bRFS, DMFS, PCSS, OS were 100%, 100%, 100% and 98.8%, respectively. Conclusion: The 2 years’ outcomes are encouraging, providing additional and useful information on the feasibility and safety of spot scanning CIRT for prostate cancer. Long term follow-up and prospective multi-institutional data are warranted to reinforce the role of CIRT in the management of localized prostate cancer.